Design and Validation of a Localized Development Model for Technical and Vocational Training Based on the Industrial Capacities of Bandar Abbas - Pakdel, Zohreh; Nami, Kolsum; Sabahizadeh, Mahmoud (Assessment and Practice in Educational Sciences, 2024)
This study aimed to design and validate a localized development model for technical and vocational education aligned with the industrial capacities of Bandar Abbas. The research employed a sequential exploratory mixed-methods approach. In the qualitative phase, data were collected through 20 semi-structured interviews with experts in technical education and industry, analyzed using thematic analysis with open, axial, and selective coding. In the quantitative phase, a researcher-made questionnaire based on the identified qualitative components was distributed among 374 participants, including industrial personnel and technical education professionals. The reliability and validity of the model were assessed through Cronbach’s alpha, AVE, CR, and Fornell-Larcker discriminant validity. Model fit was tested using structural equation modeling (SEM) in LISREL. Paired-sample t-tests revealed statistically significant differences (p < 0.01) between the current and desired states in 8 out of 9 key components, indicating major gaps in areas such as goal setting, training, and infrastructure. Convergent validity was confirmed with AVE values above 0.5, and reliability was supported by Cronbach’s alpha values exceeding 0.7 for all constructs. Fornell-Larcker matrix confirmed discriminant validity. The SEM results showed good model fit indices (e.g., RMSEA = 0.05, CFI = 0.98, GFI = 0.93), validating the structural integrity of the proposed model. The validated development model demonstrates strong empirical and theoretical grounding for improving technical and vocational education tailored to regional industrial needs. Its adoption could significantly enhance alignment between education outputs and labor market demands in Bandar Abbas and similar industrial contexts.